2013 IEEE International Conference on Solid Dielectrics (ICSD) 2013
DOI: 10.1109/icsd.2013.6619907
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of surface charge on direct-fluorinated polyimide films

Abstract: Polyimide film, as a special type of engineering plastic film, is a kind of basic insulating material and is widely applied in the aerial, nuclear, microelectronic industry, turn to turn insulation and turn to ground insulation of inverter-fed motors. However, with the disadvantage of organic polymer, its corona-resistance property is not good enough, which makes insulation early failures occur frequently. The existence of surface charge has a great effect on breakdown characteristic and is the main reason lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 7 publications
0
26
1
Order By: Relevance
“…Our previous research has shown that the fluorination can not only decrease surface energy for polyimide film but also change the electrical properties, such as dielectric property, work function and the trap depth [18]. As shown in Figure 6, the conductivity of fluorinated film is higher than the untreated film.…”
Section: Effect On Space Charge Behaviormentioning
confidence: 91%
See 1 more Smart Citation
“…Our previous research has shown that the fluorination can not only decrease surface energy for polyimide film but also change the electrical properties, such as dielectric property, work function and the trap depth [18]. As shown in Figure 6, the conductivity of fluorinated film is higher than the untreated film.…”
Section: Effect On Space Charge Behaviormentioning
confidence: 91%
“…The results show that the property of the interfacial charge changed a lot after the LDPE layer is surface fluorinated [17]. Our recent research has indicated that direct fluorination is also effective in modulating the electrical properties of the surface layers of polyimide film [18].…”
Section: Introductionmentioning
confidence: 92%
“…After fluorination, the fluorinated layer will be occurred on the surface of PI film [8]. The fluorination can restrain the charge accumulation in the surface layer of the specimen and accelerate the decay of surface charge, which reduces the amount of charge accumulated on the surface of the fluorinated specimen and improves the surface flashover strength of the fluorinated specimen.…”
Section: B Experimental Setupmentioning
confidence: 99%
“…PI films used in the experiment were prepared by a twostep method using 4, 4' -oxy dianiline (ODA) and pyromellitic dianhydride (PMDA) commercially available, according to the procedure described in our paper [8]. Surface fluorination of PI film was completed in a stainless reaction kettle at 55 °C using the mixture of F 2 and N 2 with 20% F 2 by volume and 0.05 MPa.…”
Section: A Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation